2021
DOI: 10.1080/17446651.2021.1945440
|View full text |Cite
|
Sign up to set email alerts
|

Levoketoconazole: a novel treatment for endogenous Cushing's syndrome

Abstract: Introduction: Endogenous Cushing's syndrome (CS) is a rare, life-threatening endocrine disorder that is caused by chronic exposure to cortisol overproduction. Levoketoconazole (Recorlev), a 2S, 4R stereoisomer of ketoconazole, is a steroidogenesis inhibitor under investigation for the treatment of CS. Areas covered: This review covers the pharmacology, efficacy, and safety of levoketoconazole for the treatment of patients with endogenous CS. Expert opinion: Based on the preclinical and clinical pharmacology fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 86 publications
(173 reference statements)
0
11
0
Order By: Relevance
“…Due to these initial promising results, the FDA recently accepted for review the application for levoketoconazole in the treatment of CD. However, more time is needed to compare its safety profile with ketoconazole [23].…”
Section: Overview Of Current Medication Strategiesmentioning
confidence: 99%
“…Due to these initial promising results, the FDA recently accepted for review the application for levoketoconazole in the treatment of CD. However, more time is needed to compare its safety profile with ketoconazole [23].…”
Section: Overview Of Current Medication Strategiesmentioning
confidence: 99%
“…The phase 3 SONICS study evaluating efficacy and safety of levoketoconazole reported no study withdrawals due to tumor growth with no change in tumor size in most patients through 12 months on treatment [ 12 , 25 ]. In this study, mean ACTH concentrations in the 80 patients with CD increased during dose titration and remained elevated through the maintenance phase.…”
Section: Postsurgical Management Of Recurrent CDmentioning
confidence: 99%
“…Baseline evaluation needed before medication start This example patient provides a good illustration of the steps to be taken before initiating osilodrostat. Obtaining potassium and magnesium levels and ECG measurements are critical both before initiating treatment, as a baseline, and during treatment with osilodrostat; this is also true with other adrenal steroidogenesis inhibitors, such as metyrapone [10,16] and levoketoconazole [12,17] or with the glucocorticoid receptor blocker mifepristone [11], to monitor for the development of low potassium or prolonged QTc on ECG. For patients starting specifically on osilodrostat, an ECG should be performed at baseline and 1 week after initiating therapy to ensure there is no QTc prolongation (although this is uncommon, as described later), in addition to checking for hypokalemia or hypomagnesemia and, if present, correcting these before beginning treatment.…”
Section: Clinical Case Pointsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, based on remission rates, osilodrostat appears to have the highest efficacy, followed by metyrapone, ketoconazole and levoketoconazole. A direct comparison between the racemic ketoconazole and the selective levoketoconazole is not available at clinical levels; however, experimental studies seem to suggest that levoketoconazole displays a higher potency in inhibiting adrenal enzymes compared to dextroketoconazole and to racemic ketoconazole, potentially allowing lower doses of levoketoconazole to achieve the same efficacy of ketoconazole [ 28 , 29 ]. Moreover, levoketoconazole showed a lower potency toward liver enzymes inhibition compared to dextroketoconazole, suggesting an improved safety profile of levoketoconazole on liver function [ 28 ].…”
Section: Opinionmentioning
confidence: 99%